CHRISTIAN DOCUMENTS OF BARBARISM: A HISTORIOGRAPHICAL ROADMAP OF THEOLOGICAL RESPONSES TO CHRISTIAN SUPPORT OF SLAVERY - Slatterya, John P. (Cultural encounters, 2019)
The church's many failings when it comes to racism can be traced to a warping of Christianity and Christian theology in history, especially including European and North American theologies written during and after the creation of the transatlantic slave trade. This historiographical essay offers both tools to understand the contemporary landscape of anti-racist theology and possibilities to help heal the wounds of the body of Christ. The essay is thus divided into parts. The first part, Understanding, highlights several important historical, sociological, and theological constructions of chattel slavery. Only after gaining understanding can we honestly approach the second part, Possibilities, which analyzes and categorizes a wide range of theological attempts to come to grips with rebarbative aspects of otherwise holy theologians of the past